Fetal exposure to famine increases the risk of cardiovascular disease in adulthood: findings from a population-based screening study - Li, Hui; Qi, Minjie; Yang, Shuxian; Zhang, Hanxue; Chang, Liang; Gao, Yan; Fan, Lei; Kang, Kai (Frontiers in Cardiovascular Medicine, 2025)
IntroductionUndernutrition during early life may increase the risk of chronic diseases in adulthood. The study aimed to investigate whether fetal exposure to famine would increase the risk of cardiovascular disease (CVD) in adulthood.Materials and methodsData were collected from 16 sites in Henan by the China Patient-centered Evaluative Assessment of Cardiac Events (PEACE) Million Persons Project. The famine-exposed group was defined as participants born between 1 January 1959 and 31 December 1961, and the non-exposed group was defined as participants born between 1 January 1955 and 31 December 1957, and those born between 1 January 1963 and 31 December 1965. Multivariate logistic regression models were used to explore the association between fetal exposure to famine and CVD in adulthood, with adjustments for age, sex, education, family’s annual income, currently smoking, drinking alcohol, body mass index, anti-hypertensive drugs, anti-diabetic drugs, and lipid-lowering drugs.ResultsFetal exposure to famine increased the risk of total CVD [odds ratio (OR) = 1.25, 95% confidence interval (CI): 1.14–1.38], coronary heart disease (OR = 11.25, 95% CI: 1.05–1.47), stroke (OR = 11.22, 95% CI: 1.09–1.36), and 10-year CVD risk (OR = 11.22, 95% CI: 1.14–1.31) compared with the non-exposed group. The stratified analysis suggested that after being exposed to famine in the fetal period, men had a higher risk of CVD than women in adulthood (men: OR = 11.26, 95% CI: 110–1.44; women: OR = 11.23, 95% CI: 1.12–1.35) and the population in rural areas had a higher risk of CVD than that in urban areas (rural: OR = 11.30, 95% CI: 1.15–1.48; urban: OR = 11.20, 95% CI: 1.05–1.39).DiscussionFetal exposure to famine increased the risk of total CVD, coronary heart disease, stroke, and 10-year CVD risk in Henan. The association was more pronounced in men and rural areas.